The causality of gut microbiota on onset and progression of sepsis: a bi-directional Mendelian randomization analysis - Gao, Yuzheng; Liu, Lidan; Cui, Yuning; Zhang, Jiaxin; Wu, Xiuying (Frontiers in Immunology, 2024)
Several observational studies have proposed a potential link between gut microbiota and the onset and progression of sepsis. Nevertheless, the causality of gut microbiota and sepsis remains debatable and warrants more comprehensive exploration.We conducted a two-sample Mendelian randomization (MR) analysis to test the causality between gut microbiota and the onset and progression of sepsis. The GWAS summary statistics for 196 bacterial traits were extracted from the MiBioGen consortium, whereas the GWAS summary statistics for sepsis and sepsis-related outcomes came from the UK Biobank. The inverse-variance weighted (IVW) approach was the primary method used to examine the causal association. To complement the IVW method, we utilized four additional MR methods. We performed a series of sensitivity analyses to examine the robustness of the causal estimates.We assessed the causality of 196 bacterial traits on sepsis and sepsis-related outcomes. Genus Coprococcus2 [odds ratio (OR) 0.81, 95% confidence interval (CI) (0.69-0.94), p=0.007] and genus Dialister (OR 0.85, 95%CI 0.74-0.97, p=0.016) had protective effect on sepsis, whereas genus Ruminococcaceae UCG011 (OR 1.10, 95%CI 1.01-1.20, p=0.024) increased the risk of sepsis. When it came to sepsis requiring critical care, genus Anaerostipes (OR 0.49, 95%CI 0.31-0.76, p=0.002), genus Coprococcus1(OR 0.65, 95%CI 0.43-1.00, p=0.049) and genus Lachnospiraceae UCG004 (OR 0.51, 95%CI 0.34-0.77, p=0.001) emerged as protective factors. Concerning 28-day mortality of sepsis, genus Coprococcus1 (OR 0.67, 95%CI 0.48-0.94,p=0.020), genus Coprococcus2 (OR 0.48, 95%CI 0.27-0.86, p=0.013), genus Lachnospiraceae FCS020 (OR 0.70, 95%CI 0.52-0.95, p=0.023) and genus Victivallis (OR 0.82, 95%CI 0.68-0.99, p=0.042) presented protective effect, whereas genus Ruminococcus torques group (OR 1.53, 95%CI 1.00-2.35, p=0.049), genus Sellimonas (OR 1.25, 95%CI 1.04-1.50, p=0.019) and genus Terrisporobacter (OR 1.43, 95%CI 1.02-2.02, p=0.040) appeared harmful effect. Furthermore, genus Coprococcus1 (OR 0.42, 95%CI 0.19-0.92, p=0.031), genus Coprococcus2 (OR 0.34, 95%CI 0.14-0.83, p=0.018) and genus Ruminiclostridium6 (OR 0.43, 95%CI 0.22-0.83, p=0.012) were associated with lower 28-day mortality of sepsis requiring critical care.This MR analysis unveiled a causality between the 21 bacterial traits and sepsis and sepsisrelated outcomes. Our findings may help the development of novel microbiota-based therapeutics to decrease the morbidity and mortality of sepsis.